2014
DOI: 10.1016/j.slsci.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Cataplexy as a side effect of modafinil in a patient without narcolepsy

Abstract: Narcolepsy is a disease in which there is diurnal excessive sleepiness with sleep attacks and a prevalence in the general population of 1/4000 individuals. Classically, it is characterized by cataplexy, sleep paralysis, hypnagogic hallucinations and fragmented sleep. The use of modafinil in the treatment of narcolepsy is the first option of treatment for diurnal excessive sleepiness.Although considered a safe drug for use in patients with narcolepsy, being utilized for more than 20 years, modafinil possesses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Our findings suggest that, although infrequent, cataplexy still affects many people who do not have narcolepsy. It has been previously shown that certain diseases (eg, viral encephalopathy) [ 26 ] and/or medication use (eg, lamotrigine, clozapine, modafinil) can cause cataplexy [ [27] , [28] , [29] , [30] ]. Interestingly, hypersomnolence symptoms that resemble an on/off switch, such as sudden and irresistible sleep during the day or easily falling asleep anywhere, reflect other aspects of hypersomnolence with low (albeit significant) correlations with the ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that, although infrequent, cataplexy still affects many people who do not have narcolepsy. It has been previously shown that certain diseases (eg, viral encephalopathy) [ 26 ] and/or medication use (eg, lamotrigine, clozapine, modafinil) can cause cataplexy [ [27] , [28] , [29] , [30] ]. Interestingly, hypersomnolence symptoms that resemble an on/off switch, such as sudden and irresistible sleep during the day or easily falling asleep anywhere, reflect other aspects of hypersomnolence with low (albeit significant) correlations with the ESS.…”
Section: Discussionmentioning
confidence: 99%
“…13 Secondly, all antidepressants used to treat cataplexy in patients with NT1 are known to be associated with decreased libido, erectile dysfunction, delayed orgasm or anorgasmia and delayed ejaculation. 14 Moreover, cataplexy, which has been described as an adverse reaction to modafinil in a patient without narcolepsy, 15 has also been reported as an uncommon side effect of pitolisant. 12 In our case, the patient has never reported changes in his sexual drive; partial cataplexy was already present when he started the treatment with modafinil and it remained unchanged for several years; orgasmolepsy appeared at a time of global worsening of the disease; finally, he clearly showed a dose-related response on both partial cataplexy and orgasmolepsy with pitolisant.…”
Section: Discussionmentioning
confidence: 99%
“…Эффективность модафинила для лечения патологической сонливости была показана в плацебо-контролируемых исследованиях на пациентах как в амбулаторных, так и стационарных условиях. Рекомендуемой дозой для лечения является 200 мг [46,54,58,66].…”
Section: показания к применениюunclassified